118k views
1 vote
Solve the following equation for v.

Solve the following equation for v.-example-1

2 Answers

3 votes

b+(v^2)/(2d)=T\ \ \ |-b\\\\(v^2)/(2d)=T-b\ \ \ |\cdot2d\\\\v^2=2d(T-b)\to v=\pm√(2d(T-b))
User Cassie Meharry
by
5.6k points
3 votes
Do the opposite of PEMDAS. First subtract b from both sides.

T = b + v²/2d

T (-b) = b (-b) + v²/2d

T - b = v²/2d

Multiply 2d to both sides

2d(T - b) = v²/2d(2d)

2d(T - b) = v²

Distribute 2d to both T and -b

2dT - 2db = v²

Isolate the v, root both sides

√(2dT - 2db) = √v²

v = √(2dT - 2db)

hope this helps
User Switchkick
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.